2017
DOI: 10.1055/s-0042-122386
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostik und Therapie des Vestibularisschwannoms – eine interdisziplinäre Herausforderung

Abstract: Vestibular schwannomas expand slowly in the internal auditory canal, in the cerebellopontine angle, inside the cochlear and the labyrinth. Larger tumors can displace and compress the brainstem. With an annual incidence of 1:100 000 vestibular schwannoma represent 6-7% of all intracranial tumors. In the cerebellopontine angle they are by far the most neoplasm with 90% of all lesions located in this region. Magnetic resonance imaging (MRI), audiometry, and vestibular diagnostics are the mainstays of the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 98 publications
1
19
0
6
Order By: Relevance
“…VS, also known as acoustic schwannoma, originates from the myelin-forming Schwann cells that surround the vestibular branches of the eighth (auditory) cranial nerve ( 70 ). VS accounts for 6-7% of all intracranial tumors, 90% of which are located in the cerebellopontine angle ( 71 ). Yang et al ( 46 ) demonstrated the anticancer effect of AIL in human VS cells.…”
Section: Ailanthone (Ail) As An Anti-tumor Drugmentioning
confidence: 99%
“…VS, also known as acoustic schwannoma, originates from the myelin-forming Schwann cells that surround the vestibular branches of the eighth (auditory) cranial nerve ( 70 ). VS accounts for 6-7% of all intracranial tumors, 90% of which are located in the cerebellopontine angle ( 71 ). Yang et al ( 46 ) demonstrated the anticancer effect of AIL in human VS cells.…”
Section: Ailanthone (Ail) As An Anti-tumor Drugmentioning
confidence: 99%
“…ANs, also known as vestibular schwannomas, are most typically benign, slow-growing tumors, accounting for approximately 6 to 7% of all intracranial tumors and as the most frequent lesions to occur in the cerebellopontine angle. 19 Although these tumors can be found in all patients regardless of age and gender, they are most commonly diagnosed between the third and fifth decades of life, and the annual incidence rate affects approximately 1 in every 100,000 persons. 20 Despite their benign histology and growth rate, these tumors may cause considerable symptoms for patients, given their critical location along the skull base and abutting the brain stem.…”
Section: Brief Background Of Acoustic Neuromasmentioning
confidence: 99%
“…Although there are no established guidelines to dictate surgery versus radiation, microsurgery is usually considered in symptomatic patients, favored in those who are relatively younger (<70 years of age) and/or with larger tumors (>2.5 cm). 19 Likewise, patient medical comorbidities play an important role in deciding treatment. Despite general guidelines for observation versus treatment in ANs, 21 practice patterns continue to vary widely throughout the country and the optimal management of these tumors continues to be an ongoing focus of debate, 19,21 outside the scope of this article.…”
Section: Brief Background Of Acoustic Neuromasmentioning
confidence: 99%
See 1 more Smart Citation
“…Eine Fazialisparese ist trotz der engen Beziehung der beiden Nerven zueinander eher selten [11]. Zephalgien sind eher untergeordnet (11 %).…”
Section: Fazialisparese Und Weitere Beeinträchtigungen Des Nervensystemsunclassified